Carboxymethyl Chitosan Capped Bimetallic Nanoparticles Entrapped in Theranostic Nanofibers: Antimicrobial Peptide Coating, In Vitro, In Vivo Characterization for MDR Microbial Infection and Photoacoustic/Optical Imaging - Malik A.K.; Setia A.; Verma D.; Viswanadh M.K.; Mukherjee A.; Muthu M.S. (My University, 2025)
Wound dressings, integrated with nanotechnology, have garnered considerable attention recently due to their ability to synergistically combine antimicrobial efficacy with wound healing properties, while also supporting adherence to standardized wound care protocols. We have developed smart theranostic wound dressings composed of carboxymethyl chitosan coated gold-silver-LL37 nanoparticles (G-S-CMC-Pep-NPs), of 155.1 ± 11.2 nm in size and a charge over the surface of +34.6 ± 3.7 mV. The optimized G-S-CMC-Pep-NPs were observed to exhibit minimal inhibitory and bactericidal concentration in the range of 0.390-0.781 μg/mL, also illustrated the maximum zone of inhibition (ZOI) of 21.61 ± 1.06 and 18.85 ± 1.22 mm, toward multidrug resistant (MDR) bacteria of P. aeruginosa and S. aureus respectively. TEM analysis of the microbial cells post-12-h treatment revealed irregularly undulating and disrupted cell walls, loss of cell wall integrity, and evidence of DNA condensation. Additionally, hemolysis assays demonstrated that G-S-CMC-Pep-NPs exhibited a nonhemolytic profile when tested on rodent blood, indicating their excellent biocompatibility. Furthermore, G-S-CMC-Pep-NPs were uniformly integrated into chitosan poly(vinyl alcohol) nanofibers (G-S-CMC-Pep-NPs-NFs) having a size ranging from 100 to 350 nm, resulting in an antimicrobial wound dressing, when applied to microbial-infected wounds in mice, achieved a 92.4% wound closure rate within 12 days of treatment. Additionally, this study is further substantiated through the analysis of wound marker protein expression levels, along with in vivo optical and ultrasound/photoacoustic imaging. The ultrasound/photoacoustic imaging offered an in-depth evaluation of the complex wound healing mechanism, enabling real-time visualization, high-resolution spatial imaging, and precise assessment of blood flow dynamics. © 2025 American Chemical Society.